2005
DOI: 10.1089/cbr.2005.20.349
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynoviorthesis in Osteoarthritis and Other Disorders with Concomitant Synovitis in Comparison to Rheumatoid Arthritis

Abstract: Although slightly more efficient in rheumatoid arthritis, RSO represents an effective treatment option also in osteoarthritis and other disorders with concomitant synovitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
10
0
9
Order By: Relevance
“…Various infl uencing factors on the success of RSO have been studied to defi ne its indications [2][3][4][5][6][7][8][9][10]. These include age, sex, joint size, underlying disease, type of radionuclide, additional injection of glucocorticoid, oligo-articular or polyarticular involvement, disease progression, radiological joint damage (Larsen scale), instability and/or axial deviation, body mass index, and psychological motivation for prosthesis implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various infl uencing factors on the success of RSO have been studied to defi ne its indications [2][3][4][5][6][7][8][9][10]. These include age, sex, joint size, underlying disease, type of radionuclide, additional injection of glucocorticoid, oligo-articular or polyarticular involvement, disease progression, radiological joint damage (Larsen scale), instability and/or axial deviation, body mass index, and psychological motivation for prosthesis implantation.…”
Section: Introductionmentioning
confidence: 99%
“…By means of placebo-designed studies, it has been shown that RSO appears to be superior to the sole injection of 1 3 glucocorticoid [5,10,11]. However, some results are controversial regarding the superiority to the sole glucocorticoid injection, concerning the knee [12] and the success rate in general [4,8,12,13]. Furthermore, the reported success rates range from 40% to 100% in the literature [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life improved in 78 % of group A and 59 % of group B (p \ 0.01). Conclusion: Although slightly more efficient in RA, RSO represents an effective treatment option also in OA and other disorders with concomitant synovitis (Rau et al 2004).…”
Section: Resultsmentioning
confidence: 94%
“…Биологическое действие на воспаленную синовию продолжается в течение многих лет. Согласно многочис-ленным исследованиям, ответ на лечение при РА наблю-дается примерно в 80% случаев при отсутствии деструк-ций [16][17][18][19][20][21]. Поэтому терапию следует проводить по воз-можности до возникновения необратимых изменений су-ставов.…”
Section: результаты леченияunclassified